THE IMPACT OF HEAT WAVES ON THE LEVEL OF AIR POLLUTION IN KYIV - SHEVCHENKO, Olga; YATSENKO, Yuliia; KRYVOBOK, Diana; SNIZHKO, Sergiy (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2023)
Air pollution level in big cities is heavily influenced by meteorological factors, including heat waves (HWs). During the last decades, the number of HWs and their intensity has increased worldwide including in Ukraine. Heat waves are more intensive in big cities, because of manmade surfaces and fewer green zones. The aim of this study is to investigate the impact of heat waves on the level of air pollution in Kyiv.The research is based on the concentrations of formaldehyde, nitrogen dioxide, and sulfur dioxide measured on 6 monitoring stations during the summer months of 2017–2021 in Kyiv. These monitoring stations are characterized by very different concentrations of air pollutants. Data from daily observations of maximum air temperature for the periods 1961–1990 and 2017–2021 are employed for the identification of HW episodes for the summer period. To describe pressure conditions favoring the occurrence of heat waves, daily values of sea-level pressure (SLP), the height of the geopotential height of 500 hPa, and temperature on the 850 hPa pressure surface were used. The research showed the effect of heat waves on the concentrations of nitrogen dioxide, formaldehyde, and sulfur dioxide in the air of Kyiv. The concentrations of these pollutants during the heat wave events at all studied monitoring stations (regardless of the initial level of air pollution) and a gradual decrease in concentrations after the HWs finished have been found. The circulation processes caused to the formation of HWs over the territory of Ukraine were analyzed. It was shown that during the heat waves that occurred in Kyiv within the years 2017–2021, in all cases, except for one, the baric field formed over the studied territory had almost the same structure and shape. It is confirmed that the formations of heat waves in Kyiv are associated with anticyclonic formations in the atmosphere. Therefore, the influence of heat waves on the concentrations of formaldehyde is explained by the fact that during the HWs, there are very favorable conditions for the course of photochemical reactions from precursor substances, which leads to an increase in the concentration of this pollutant, while the influence on the concentrations of sulfur dioxide and nitrogen dioxide is caused by the fact that heat waves are characterized by all features of anticyclonic weather (like low wind speeds (or calm), inversions, etc.) which are favorable conditions for the accumulation of pollutants in the atmosphere.
Keywords: heat wave; air pollution; nitrogen dioxide; sulfur dioxide; Kyiv